Implementasi Kepemimpinan Kepala Sekolah Perempuan Di SD YPPK Santo Mikhael Mugouda Distrik Tigi Kabupaten Deiyai Provinsi Papua Tengah - Anselma Doo; Kusdianto; Albaiti (JURNAL PASTORAL KATEKETIK, 2024)
The purpose The purpose of this study was to examine and describe the Implementation of the Leadership of the Female Principal according to Bush and Coleman's statement (2012: 102) at YPPK Santo Mikhael Mugouda Elementary School in terms of: 1) Attention to people in the school and their workload, 2) Building work together, sharing, and working in a team, 3) Doubtful attitude, not satisfied with work, 4) Status.The research method used in this study is a qualitative research method. Data collection techniques were carried out through observation, documentation and interviews. The results of the study showed that the leadership of the female school principal at SD YPPK Mugouda, Tigi district, Deiyai district, had shown her leadership skills with female teachers in a society with a patriarchal socio-cultural life, based on the theory of Bush and Colmen (2012) that: First, women can lead and organize education. The ability to lead school principals has been carried out in terms of attention, namely: 1) Giving attention in the form of services to students is shown through motherhood and motivating subordinate teachers by paying attention to workload in the form of honorariums and awards. 2) Give attention to students and teachers through their role as educators. 3) Invite parents to pay attention to the workload of teachers and students. 4) Make donations to the community (church) on behalf of the school. The two female leaders are capable of holding meetings, receiving opinions, making decisions to work on together. His ability is shown by building cooperation, sharing and working in a team with three parties, namely: 1) The first party is with the teachers through work meetings. 2) The second party together with the teachers and students carried out the results of the meeting and 3) The third party together with parents and the school committee through meetings, produced a mutual agreement and carried it out. Like a spinning wheel, in the process and time of implementation, joint meetings become an opportunity to discuss, share expectations and constraints, find solutions and make agreements to carry out programs in the form of cooperation and team work.